Effect of Variety and Spraying With Seaweed and Color of Plastic Cover on Growth and Yield of Potato (Solanum tubersum L.) on Autumn Lug - Essa, Nawras Hassan; Anjal, Sabeeh Abdulwhab; Abood, Mohammed Ail (Journal of agricultural, environmental and veterinary sciences, 2019)
A field Experiment was conducted during the autumn agricultural season 2018 at Horticulture and Gardening Engineering – College of Agriculture, Diyala University of study the effect of variety and spraying with seaweed and the color of plastic cover on the growth and yield of potato. The experiments were arranged in a Nested combined design with three replications Randomized Completely Block design (RCBD) used.it include the experiment three factors.the first category two types Dutch origin species (Arizona and fandango, a Scottish origin species, and the second factor is three concentrations of seaweed extract (Phylgreen mira) (0, 2.5 ,5 ml. L- 1 ) , the Third factor: three transaction of Coverage the without coverage is the comparison treatment and the coverage with white polyethylene (transparent) and coverage balbola yellow ethylene. show the results outweigh the product was Arizona variety and Spray with concentration 2.5 ml. L- 1 and cover with yellow cover a significant superiority at the rate of, number of total tubers per plant , number of marketable tubers ,total plant yield , one marketable plant yield, marketable yield, total tubers yield which was to13.800 tubers Plant- 1 , 13.066 tubers Plant- 1, 1002.00 g plant- 1 , 974.67 g plant- 1 , 64.973 ton.ha- 1 , 66.800 ton.ha- 1 respectively.
Keywords: Variety; Seaweed; Yield; Potato in plastic house